2010
DOI: 10.1261/rna.2244210
|View full text |Cite
|
Sign up to set email alerts
|

RNase L releases a small RNA from HCV RNA that refolds into a potent PAMP

Abstract: Triggering and propagating an intracellular innate immune response is essential for control of viral infections. RNase L is a host endoribonuclease and a pivotal component of innate immunity that cleaves viral and cellular RNA within single-stranded loops releasing small structured RNAs with 59-hydroxyl (59-OH) and 39-monophosphoryl (39-p) groups. In 2007, we reported that RNase L cleaves self RNA to produce small RNAs that function as pathogen-associated molecular patterns (PAMPs). However, the precise sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
118
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 53 publications
2
118
1
Order By: Relevance
“…The fact that RIG-I can respond to the RNAs made in the presence of VPg raises questions about ligand recognition by RIG-I. RIG-I also recognizes viral RNAs processed at their 3Ј terminus by the endoribonuclease RNase L, which leaves a 3Ј-phosphate in the RNA (40,41). Therefore, we examined whether RNase L can process VPg-linked RNAs in the context of the NoV-5BR assay.…”
Section: Rnas Synthesized By Nov Rdrp Can Induce Signaling By Rig-imentioning
confidence: 99%
“…The fact that RIG-I can respond to the RNAs made in the presence of VPg raises questions about ligand recognition by RIG-I. RIG-I also recognizes viral RNAs processed at their 3Ј terminus by the endoribonuclease RNase L, which leaves a 3Ј-phosphate in the RNA (40,41). Therefore, we examined whether RNase L can process VPg-linked RNAs in the context of the NoV-5BR assay.…”
Section: Rnas Synthesized By Nov Rdrp Can Induce Signaling By Rig-imentioning
confidence: 99%
“…The redundancy of the antiviral IFN system likely results in relatively modest phenotypes when individual ISGs are deleted compared to the targeted knockout of the type I IFN receptor, pathogen recognition receptors, or key IRF signaling intermediates (11,44), which initiate the induction of hundreds of ISGs. Previous experiments in mice showed that the deletion of PKR, RNase L, or OAS1b correlated with increased susceptibility to WNV in mice (33,37,46), although more recent works suggested that at least some of the phenotypes (for PKR and RNase L) could be due to amplification rather than an execution of IFN signals (31,32,49). Given the increasing number of putative antiviral ISGs that regulate infection by WNV and other viruses (48), the expectation that the targeted deletion of any single gene will have dramatic effects may be unrealistic, and the more modest phenotype observed with viperin Ϫ/Ϫ mice should be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Retinoic acid-inducible gene I (RIG-I) (14), IFN-induced proteins with tetratricopeptide repeats (IFITs) (15), and the double-stranded RNA-dependent protein kinase (PKR) can recognize 5′triphosphates (5′ppp)-bearing viral RNA in the cytoplasm (16). Antiviral signaling is also induced by modified self-RNAs under physiological stress conditions (17)(18)(19). Removal of proinflammatory self-RNAs, while maintaining the ability to selectively recognize virus-produced RNAs in the cell's cytoplasm, is essential for proper regulation of antiviral response.…”
Section: Significancementioning
confidence: 99%